Assessing the grey water footprint of pesticide use in the Mendoza wine region (Argentina): implications for sustainable water resources management - Verónica Farreras; Belén Lana; Oscar Astorga (OENO One)
This paper assesses the impact of viticulture on water resource quality in the Mendoza wine region using the grey water footprint (GWF) approach to estimate the amount of water required to dilute pesticides commonly used in local vineyards. Our analysis indicates that to progress towards sustainable water management in viticulture, limiting or replacing pesticides with high GWF values is essential. We provide detailed results for 24 fungicides, 7 insecticides, and 7 herbicides, assessed at both microregion and district levels, offering insights into pesticide impacts across both detailed and broader spatial scales. At the microregion level, the herbicide Fluroxypyr-meptyl was found to have the highest GWF (1.10 m³ kg-1), followed by the fungicide Fosetyl-aluminium (0.59 m³ kg-1) and the insecticide Imidacloprid (0.41 m³ kg-1). Our findings also show that pesticide impacts vary at the district level, highlighting the need for localised management strategies. Additionally, the significant variability in GWFs at the local level underscores the necessity for region-specific water quality standards to more accurately assess and manage the environmental impact of pesticide use. This study provides a framework for similar assessments in other viticultural regions, aiding in the development of more informed pesticide management to enhance water resource sustainability.